Nanotechnology in pediatric dermatology - Sandipan Dhar; Ramkumar Rammoorthy; Samujjala Deb; Deepak Parikh (Wolters Kluwer Medknow Publications, 2019)
Nanotechnology is the manipulation of material with size <100 μ. Application of nanotechnology in medicine is also known as nanomedicine. Nanotechnology has found varied applications in medicine, ranging from diagnostic devices, contrast agents, tools for analysis, and most importantly in the field of drug delivery.